Integral assessment of oxidative metabolism during long-term domestic revenue 131I in rats - Yu. P. Grynevych; A. I. Lypska; I. P. Drozd; S. V. Teletska (Ядерна фізика та енергетика)
Peroxy processes in the blood of male rats of the Wistar chemiluminescence method with prolonged oral intake of 131I were investigated. It has been shown that long-term oral intake of 131I (29.3 kBq/day per animal for 14 days) causes changes in the indices of the chemiluminescent reaction (aggregate chemiluminescence, luminescence maximum and the final intensity of luminescence, time to reach maximum values). However, absolute values of these indicators are not significantly dependent on the administration of the active isotope. We discuss features of the current processes of peroxidation in the blood of laboratory rats after prolonged administration of 131I.